Pembelajaran Berbasis Masalah sebagai Salah Satu Upaya Meningkatkan Kemampuan Analisis dan Penalaran Peserta Didik - Efideswati Nasution (Instructional Development Journal, 2020)
Education aims to develop the potential of students to become quality human resources. The implementation of education takes place in a learning activity. Through the learning process there will be changes, development, progress, both in terms of physical, motoric, intellectual, social emotional and attitudes and values. One of the abilities that must be developed is the analytical and reasoning skills of students, because it will be used in solving problems in everyday life. This article aims to analyze an effective learning model to improve the analytical and reasoning skills of students. This research is a literature study. Analysis of effective learning models to improve the analytical and reasoning power of students is drawn from various references and research results. It was found that one of the learning models that can improve analytical and reasoning skills is the problem-based learning model. Problem-based learning uses a variety of intelligences needed to confront the real world. Problem-based learning is an innovation in learning because in PBL the thinking ability of students is really optimized through a systematic group or team work process so that students can empower, hone, test and develop their thinking skills on an ongoing basis.